Risk factor analysis for urinary tract infection in outpatients at a hospital in Subang, Indonesia - Reginawati, Serli; Fauziah, Wardah; Minanton, Minanton (Program Studi Keperawatan, Politeknik Negeri Subang, 2023)
Background: Urinary Tract Infection (UTI) is considered an infectious disease with a high incidence rate; this is due to the individual’s lifestyle, which is a factor in the occurrence of UTI. To reduce the incidence of UTI, it can be done by knowing the risk factors that can influence the occurrence of UTI with individual awareness and practicing good habits. Purpose: to analyze the risk factors for urinary tract infection in outpatients. Methods: This research used quantitative research with a cross-sectional design that has been carried out on 89 patients who came for treatment at the Urology Polyclinic at RSUD Subang, using purposive sampling through a questionnaire on risk factors and symptoms of UTI, and then the data was analyzed using multiple linear regression tests. Results: The results of the study found that there is a relationship between age, gender, urinary retention habits, genital hygiene, and drinking habits and the incidence of UTI, with a P-value of 0.000 (P < 0.05). Conclusion: Age, gender, urinary retention habits, genital hygiene, and water drinking habits are risk factors for urinary tract infections both independently and simultaneously. Screening for UTI in outpatients, Geriatric age, female gender, urinary retention habits, bad genitourinary tract hygiene, and less water intake should be adopted.